2008
DOI: 10.1074/jbc.m806577200
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Nitrile Hydratase Proposed by Time-resolved X-ray Crystallography Using a Novel Substrate, tert-Butylisonitrile

Abstract: Nitrile hydratases (NHases) have an unusual iron or cobalt catalytic center with two oxidized cysteine ligands, cysteinesulfinic acid and cysteine-sulfenic acid, catalyzing the hydration of nitriles to amides. Recently, we found that the NHase of Rhodococcus erythropolis N771 exhibited an additional catalytic activity, converting tert-butylisonitrile (tBuNC) to tert-butylamine. Taking advantage of the slow reactivity of tBuNC and the photoreactivity of nitrosylated NHase, we present the first structural eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…Gumataotao et al showed evidence of the intermediate species using single turnover stopped-flow spectroscopy [18]. Hashimoto et al analyzed the reaction mechanism of tert-butylisonitrile (tBuNC) conversion catalyzed by NHase using time-resolved X-ray crystallography and suggested that the substrate was coordinated to the iron ion and attacked by a water molecule activated by Cys-SO (inner-sphere mechanism) [19]. Martinez et al have shown that the X-ray crystal structures of Co-containing NHase with bronic acids (inhibitors) and suggested that the oxygen atom in the cysteine-sulfenic acid could act as a nucleophile and directly react with the substrate [20].…”
Section: Introductionmentioning
confidence: 98%
“…Gumataotao et al showed evidence of the intermediate species using single turnover stopped-flow spectroscopy [18]. Hashimoto et al analyzed the reaction mechanism of tert-butylisonitrile (tBuNC) conversion catalyzed by NHase using time-resolved X-ray crystallography and suggested that the substrate was coordinated to the iron ion and attacked by a water molecule activated by Cys-SO (inner-sphere mechanism) [19]. Martinez et al have shown that the X-ray crystal structures of Co-containing NHase with bronic acids (inhibitors) and suggested that the oxygen atom in the cysteine-sulfenic acid could act as a nucleophile and directly react with the substrate [20].…”
Section: Introductionmentioning
confidence: 98%
“…6) (6,16,(22)(23)(24). The rate constants provided herein suggest a fast second-order step that involves binding of substrate to the enzyme followed by rearrangement and then product release, which is the rate-limiting step.…”
mentioning
confidence: 99%
“…Alternative mechanisms have also found support from time-resolved crystallographic and kinetic studies that involve an activated water molecule attacking the metal-bound nitrile (Fig. 1C) (7,8).…”
Section: Nitrile Hydratases (Nhases)mentioning
confidence: 97%